Asset structures for income taxation in Colombian holding companies (Revista "Boletín el Conuco", 2026)
This article analyzes income tax and complementary taxes imposed on Colombian holding companies based on their asset structures. To this end, a mixed-methods approach was used, combining a quantitative approach to characterize a sample of six companies with a qualitative approach based on interviews with three experts. The results show that asset planning is a valid strategy for tax management by Colombian holding companies, as it leverages the tax benefits provided by Colombian tax rules.
Keywords: Assets; Colombia; Holding companies